Application of Skin-stretching Device for Closing Scalp Defect. Issue 1 (10th January 2023) - Zhang, Qingtao; Xu, Lei; Liu, Yang; Tang, Xiaoyong; Wang, Jia; Deng, Yongbing; Chen, Peng
Abstract : Background: The scalp defect was a clinical common constructive challenge. This research verified the efficacy of the skin-stretching device in the treatment of scalp defect and assessed the associated complications. Methods: The clinical data of 12 patients with scalp defect treated with skin-stretching device from January 2020 to January 2021 were collected. We used EASApprox skin-stretching device for the treatment of scalp defect. We described a detailed reconstruction procedure for this treatment. We collected the site, distance from wound edge and other characteristics of the wound, and recorded the number of stretching cycles, operation time, closed state, healing time, and observed postoperative complications and wound healing status. Results: In this research, the scalp defect was mainly caused by pressure ulcer, and mainly located in the parietooccipital site. The average distance from wound edge was 3.2 cm, the average stretching cycles was 4.2 times during the operation, and the average operation time was 43.5 minutes. Ten patients were directly sutured after stretching, and 2 patients underwent first-stage stretching to reduce the wound. The average time of wound healing was 13.5 days. Postoperative follow-up of 3 months, no patients had wound tear, necrosis, 1 patient suffered from wound exudation and infection due to poor nutrition. Skin function and final scar was acceptable. Conclusion: The treatment of skin-stretching device was effective for scalp defect and has the advantages of convenient operation, acceptable functional results, without severe complications. In addition to traditional treatment, this was a promising treatment. However, more clinical and preclinical research of the skin-stretching device were required.